“Family” as a legal concept - Isabel Cristina Jaramillo Sierra; Helena Alviar (Revista CS)
The concept of “family” plays an important role in the way national legal regimes distribute both power and resources. However, the idea of what a family is or should be is not univocal for all branches of law. In this paper we wish to contribute to feminist thinking about the law and to legal theory in general, by showing the contradictions and gaps in law’s incorporation of the legal concept of the family and their distributive impact. We use the notion of conceptual fragmentation to refer to the irregular manner in which family as a legal concept lands into the realms of diverse fields of law at different moments in time and with different emphasis. We argue that conceptual fragmentation makes connections through time and subject matter invisible, and therefore makes it harder to have a critique of the role of the family, treated as a legal concept, in the oppression of women. We establish that conceptual fragmentation is not irrational or incoherent but rather patterned in ways that correspond to the losses of women in contemporary societies. We use the case of colombian law to illustrate the stakes involved in defining the family and the operations that we call fragmentation. In particular, we explain how family law exceptionalism was produced, the importance of the legal concept of the family within family law and its ambivalence as to the proper definition, and the evolution of the concept of family within social policy. We argue that even if the stakes of the family seem to be all for same sex couples, in so far as “family” is still about reproduction and distribution, we should be vigilant about how women fare in the conceptual turns that seek to bring us closer to the natural family.